PENGARUH PUPUK FOSFAT DAN PUPUK HAYATI TERHADAP PERTUMBUHAN, KOMPONEN HASIL DAN HASIL TANAMAN HANJELI PULUT (Coix lacryma-jobi L) - Tabri, Agus; Tadjudin, Endang; Sungkawa, Iman (Agroswagati : Jurnal Agronomi, 2023)
This experiment aims to determine the effect of a combination of phosphate fertilizers and biological fertilizers on the yield components and yields of hanjeli rice (Coix lacryma-jobi L.). The experiment was carried out in Mekarjaya Village, Gantar District, Indramayu Regency - West Java. The time of the research was carried out from August to January 2022. The location is located at an altitude of ±50 m above sea level (masl), the soil type is associated with latosol and regosol, including type D rain (medium). The experimental method used was the experimental method with a randomized block design with a combination pattern, the treatment consisted of two factors which were repeated three times. The main factor was the dose of phosphate fertilizer which consisted of three levels, namely 200 kg/ha, 250 kg/ha and 300 kg/ha. While the second factor is the dosage of biological fertilizers consisting of three levels, namely 5 liters/ha, 10 liters/ha and 15 liters/ha. The main observational data were processed using statistical tests of linear models, analysis of variance, and analysis of the Scott-Knot cluster test. To find out the correlation between the treatment and the yield and yield components of the plant, the correlation used is the Product Moment correlation coefficient. The experimental results showed: (1) The combination treatment of phosphate fertilizer doses with biological fertilizer doses had a significant effect on root volume, number of tillers, number of incisors, biomass, seed weight per clump and seed weight per plot, but had no significant effect on plant height, number of leaves , leaf area index and 100 seed weights (2) The combined dose of 300 kg/ha phosphate fertilizer and 10 liter/ha biological fertilizer gave the best effect on seed weight of 3.29 kg per plot (equivalent to 3.29 tons/ha) but no difference significantly on the combination of 250 kg/ha phosphate fertilizer and 15 liter/ha biological fertilizer (3) There is a moderate correlation between the number of fins per clump and seed weight per plot